PERIOD3 variable number tandem repeat genotype associations with performance, injury, illness and re-entrainment - Kunorozva, Lovemore (Department of Molecular and Cell Biology, 2017)
Background: Circadian rhythms are internally driven biological variations that fluctuate with a period of approximately 24 hours, even in the absence of external environmental time cues. These rhythms enable organisms to synchronise their internal clock time with external environmental time. This ensures appropriate timing of biological and metabolic processes, and allows anticipation of daily changes in the environment. Circadian rhythms also play an important role in sports in terms of optimising performance time-of-day and aiding adjustment to global time zone changes. Thus, performance, which is under the control of the athlete, may be impacted by event time-of-day scheduling in the new time zone. It has previously been shown that individual sport athletes in South Africa tend to be morning-types and carry the PERIOD3 (PER3) Variable Number Tandem Repeat (VNTR) 5-repeat allele, which has been associated with a preference for mornings. The distribution of the PER3 VNTR polymorphism in combination with an individual's preference for mornings or evenings has not yet been described in team sports. Differences in the PER3 VNTR genotype between team and individual sport athletes are expected, given that individual sport athletes may be free to choose the time-of-day at which they train. In contrast, team sport athletes usually train in groups, thus these individuals may not have the flexibility to choose their preferred training times. There are notable inter-individual differences in adjustment to jet-lag after time zone changes. A possible genetic candidate that may be responsible for some of this variation is the PER3 VNTR gene. This gene consist of two alleles corresponding in size to 4-repeats (PER34) or 5-repeats (PER35). Individuals are either homozygous for the 4-repeat allele (PER⁴⁄⁴) or the 5-repeat allele (PER3⁵⁄⁵), while others are heterozygous for the PER3 gene (PER34/5). The PER3 VNTR genotype might explain individual sensitivity to bright light and has been reported to be associated with sleep pressure- an increase in the brain's pressure and need for sleep, following an extended period of awakening. Individuals homozygous for the longer variant of the gene (i.e. PER3⁵⁄⁵) experience a higher sleep pressure during extended wakefulness. The PER3⁵⁄⁵ genotype has been reported to be more sensitive to the alerting and melatonin suppression effects of blue enriched light than the PER⁴⁄⁴ genotype. Aims: Therefore, the aim of Study 1 was to compare the chronotype and PER3 VNTR genotype distribution of South African Super Rugby players to individuals of low physical activity (i.e. those who are physically active ≤2 times per week). The aim of Study 2 was to determine whether PER3 VNTR genotype might contribute to inter-individual variation in the extent to which game involvement and quality of play are affected following trans-meridian travel. Further, the aim of Study 3 was to compare the impact of time zone travel during the 2012 Super Rugby competition in South African players genotyped as PER⁴⁄⁴, PER34/5 and PER3⁵⁄⁵ on the incidence of illnesses and injuries. Lastly, the aim of Study 4 was to compare the extent to which individuals genotyped as PER⁴⁄⁴ or PER3⁵⁄⁵ respond to appropriately-timed blue light exposure in order to resynchronise their circadian rhythm, following simulated eastward travel, based on changes in dim-light melatonin onset and cortisol circadian phases.